Joycean Multimodalities: A Preliminary Investigation of Giacomo Joyce. - McCourt, John (Journal of Modern Literature)
Presents a preliminary investigation of "Giacomo Joyce," James Joyce's slim Triestine poem-in-prose. Description of the stylistic and modal ambivalence in the prose lyrics of "Giacomo Joyce"; Joyce's use of the present tense as the chief narrating tense; Argument of Hauser that Joyce's use of montage achieves a level of aesthetic autonomy; Analysis of size of manuscript, script usage, paragraph and clause construction for lexical cohesion; Need for hypermedia analysis.